Vagal modulation after training at different levels of the Pilates method - de Souza Cavina, Allysiê Priscilla [UNESP] (2025)
Introduction: cardiovascular and autonomic adjustments occur during and after physical exercise, and exercise intensity can directly influence the magnitude of these adjustments. Therefore, it is important to analyze post-exercise recovery to provide better guidance for prescription strategies. Objective: to analyze autonomic behavior during post-exercise recovery after the Pilates method at different intensity levels. Methods: in total, 24 healthy young men were included in this study. The participants underwent 12 weeks of Pilates training. The exercises were progressive between beginners, intermediate, and advanced levels. Post-exercise autonomic behavior was analyzed using vagal indices of heart rate variability. Descriptive statistics were adopted with Repeated Measures Analysis of Variance and the Bonferroni correction. Results: for intermediate and advanced levels, a decrease in vagal modulation was observed (p < 0.05) in the first 5 min after exercise compared to rest, represented by the rMSSD and SD1 indices. Conclusion: intermediate and advanced exercise reduced parasympathetic modulation in the initial minutes of post-exercise recovery. The beginner level did not promote changes in autonomic behavior immediately after the exercise session.